Non-formal disaster education programs for school students in Iran: A qualitative study of the challenges experienced by stakeholders. (15th February 2023) - Seddighi, Hamed; Lopez Lopez, Monica; Zwitter, Andrej; Muldoon, Meghan L.; Sajjadi, Homeira; Yousefzadeh, Sepideh
Abstract: This study aims at identifying challenges of the existing disaster preparedness education programs for children in Iran. There are two main non-formal disaster education programs for preparing children for disasters: The Earthquake and Safety School Drill Program (ESSD) and Ready Students for Severe Days, or DADRAS. To implement these programs, different organizations work together. 48 interviewees participated in this study, including school students and staff with various roles at Red Crescent and Ministry of Education, as well as school principals, Red Crescent volunteer trainers, Medical Emergency Organization staff, and Fire Department staff. Data was analyzed with narrative qualitative analysis. When analyzing qualitative data, fourteen challenges were identified in providing disaster preparedness programs to school children. The main challenges of disaster education programs in Iran are Communication (stakeholder communication, stakeholders' recognition, informing of stakeholders, and reliability), planning (sustainable planning, time table, inclusivity, educational resources), coordination (inter-organizations, intra-organizations), and logistics (staff, trainers, equipment, budget). According to our findings, programs should be upgraded to cover all Iranian children and should be prioritized in budget allocation and distribution. They require more facilities, and structure. Inclusivity aspect of the programs need more attention, and no child should be left out of disaster education, including children who are not in school, children in exceptional schools, and children in juvenile detention centers. Governments are recommended to prepare children for various disasters and do not focus only on earthquakes with an all-hazard approach.